The Tragedy of Great Power Politics - Mearsheimer, John J. (New York W.W Norton & Company, 2001)
An analysis of the inevitability of war. As the Cold War fades, leaders and theorists alike speak of a new era, when democracy and open trade will join hands to banish outright war. Mearsheimer exposes the truth behind this rhetoric: in a world where no international authority reigns, hegemony is the only insurance of security.
Include Index
Keywords: World politics -- International relations -- Great powers